Neem leaf glycoprotein mediated immunomodulation and epigenetic regulation in Acute Myeloid Leukemia - Roshni Bibi; Shreyoshi Das; Subham Swopnil Deo; Srijita Sen; Sana Praveen; N. M. Pujitaa; R. Pradeep; Melvin George; Koustav Sarkar (Molecular Biology Reports, 2026)

Magnesium biomineralization and glushinskite synthesis in fungi: possible impact on niche exclusion, role in fungi mediated detoxification and future applications - Saptaswa Chakraborty; Subham Sarkar; Hailah M. Almohaimeed; Zuhair M. Mohammedsaleh; Arup Kumar Mitra; Bikram Dhara (Antonie van Leeuwenhoek, 2026)

Importance of the inflammasome in gut-brain axis: from pathological driver to therapeutic target - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Inflammopharmacology, 2026)

Exosomes-mediated intercellular communication and their theragnostic potential against cancer and related disorders: a comprehensive review - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Biotechnology Letters, 2026)

Signatures of Oncosomes as dual-function nanocarriers in targeted drug delivery and early cancer detection - Popat Mohite; Nobendu Mukerjee; Abhijeet Puri; Subham Sarkar; M.M. Rekha; Mayank Kundlas; Mukesh Kumari; Rohit Sharma; Nanasaheb D. Thorat; Parshant Kumar Sharma (Chemical Engineering Journal, 2026)

Exploring the roles of fungal extracellular vesicles in fungal pathogenesis and symbiosis: Current understandings and future perspectives - Subham Sarkar; Aishee Hazra; Bikram Dhara; Entaj Tarafder; Arup Kumar Mitra (World Journal of Microbiology and Biotechnology, 2026)

Growth enhancement and rhizosphere colonization of Chilli (Capsicum annuum) by Enterobacter hormaechei - Bikram Dhara; Entaj Tarafder; Dong-Qin Dai; Subham Sarkar; Ayush Bagchi; Upasana Ghosh; Liana Mukherjee; Aishee Hazra; Arup Kumar Mitra (World Journal of Microbiology and Biotechnology, 2026)

Spermidine Attenuates Neuroimmune Dysfunction in Gulf War Illness via Modulation of the Gut- Brain Axis - Ayushi Trivedi; Subhajit Roy; Madhura More; Dipro Bose; Punnag Saha; Ram Kumar; Subham Sarkar; Jonathan Skupsky; Ashok Tuteja; Kimberly Sullivan; Nancy Klimas; Saurabh Chatterjee (Molecular Neurobiology, 2026)
Gulf War illness (GWI) affects nearly one-third of US veterans deployed during the 1990–1991 Gulf War (GW) and is characterized by chronic fatigue, neuroinflammation, and gut dysbiosis. Through comprehensive fecal metabolomics sequencing, our lab previously reported the depletion of beneficial metabolites including spermidine in the preclinical GWI mouse model. Spermidine is an endogenously synthesized polyamine known for its anti-inflammatory and mucosal barrier protective effects in various pathological diseases. Given its established role in mitigating intestinal inflammation and maintaining homeostasis, this study investigated the therapeutic potential of spermidine in a persistent (22 weeks) GWI mouse model, with a specific focus on gut–brain axis regulation. Our results demonstrated that spermidine effectively restored both microbial richness and diversity by selectively enriching beneficial bacterial taxa and suppressing growth of opportunistic pathogens, which are otherwise dysregulated following exposure to GW chemicals. Spermidine treatment also improved gut epithelial barrier integrity and reduced epithelial release of high-mobility group box 1 (HMGB1) into systemic circulation. Recent studies on GWI have implicated a critical role of gut-derived damage-associated molecular patterns (DAMPs), particularly HMGB1 in mediating neuroinflammation. Our findings indicate that systemic levels of HMGB1 critically influence the extent of blood–brain barrier (BBB) disruption and subsequent microglial activation. Mechanistically, spermidine activated intestinal aryl hydrocarbon receptor (AhR)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling, which played a role in limiting intestinal HMGB1 release and suppressing downstream receptor for advanced glycation end-product (RAGE)–mediated microglial activation in the brain. In vitro results indicate spermidine promoted AhR/Nrf2 nuclear translocation which reduced LPS-induced HMGB1 release from primary intestinal epithelial cells (IECs), effects abrogated by AhR inhibition. Additionally, we observed that HMGB1 directly induces microglial activation via RAGE receptors in immortalized microglial (IMG) cell lines in a dose-dependent manner. These results demonstrate that spermidine decreases neuroinflammation by modulating gut–brain axis pathophysiology associated with GWI. Together, this study demonstrates the therapeutic role of spermidine in ameliorating systemic and neurological disturbances in GWI. Graphical Abstract

Arbuscular mycorrhiza symbiosis—from molecular dialogues to biotechnological applications - Subham Sarkar; Souvik Roy; Lopamudra Choudhury (Mycological Progress, 2025)

Efficient bio-valorization of rice straw via integrated fungal biorefinery: Linking lignocellulose fractionation and nanomaterial development for sustainable agricultural application - Jit Sarkar; Subham Sekhar Mandal; Pralay Maiti; Krishnendu Acharya (Chemical Engineering Journal, 2025)

Detection and in silico characterization of banana bunchy top virus in West Bengal, India: relevance to global genetic diversity and population structure - Swati Chakraborty; Subham Dutta; Mritunjoy Barman; Snigdha Samanta; Krishna Pada Sarkar; R. Poorvasandhya; Jayanta Tarafdar (VirusDisease, 2023)

Terrestrial Martian Analog Heritage of Kachchh Basin, Western India - Anil Chavan; Subham Sarkar; Adarsh Thakkar; Jaymeet Solanki; Chirag Jani; Subhash Bhandari; Satadru Bhattacharya; Bhawanisingh G. Desai; Dwijesh Ray; Anil D. Shukla; K.S. Sajinkumar; Souvik Mitra; et al. (Geoheritage, 2022)

Seismic profile analysis of the Kangra and Dehradun re-entrant of NW Himalayan Foreland thrust belt, India: A new approach to delineate subsurface geometry - Joyjit Dey; R Jayangonda Perumal; Subham Sarkar; Anamitra Bhowmik (Journal of Earth System Science, 2017)

Seasonal dynamics of Vibrio cholerae and its phages in riverine ecosystem of Gangetic West Bengal: cholera paradigm - Subham Mookerjee; Abhishek Jaiswal; Prasenjit Batabyal; Marc H. Einsporn; Ruben J. Lara; Banwarilal Sarkar; Sucharit Basu Neogi; Anup Palit (Environmental Monitoring and Assessment, 2014)